(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The linguistic object of research is the systemic ties of the plane of text content. The hypothesis of the research is as follows: the principle of repeatability of symmetric and asymmetric elements in the system of semantic and syntactic ties and the relations, demonstrates internal harmony of the text. The harmonious organization of the art text that transfers the esthetic intentions of the author is implemented in the principle of constructing the text as a structural object where the laws of symmetry come to power. Mathematical laws operating the nature provide the source of symmetry as a philosophical category, and the intuitive realization of this idea in the creative spirit of the artist serves as a source of symmetry in art. From numerous types of symmetry in the harmonious organization of the art text employed are figurative and mirror forms of symmetry. The asymmetric constructions, which are characterized by a significant lack of similar and commensurable syntactic patterns within one statement, can also act as a principle of the harmonious organization of the text. They promote the transfer of subjective esthetic information and increase the information capacity of the text. To expressive modifications of the syntactic constructions, functioning in complex syntactic unities (dicteme), belongs parceling structures constructed on the principle of asymmetry. Modeling of the composite structure, in which a certain sequence of structural types of the sentence is fixed, the system of their bonds and the logical relations reduce the entropy of a statement, objectivize the information of such structures and increase the informational capacity of the art text. Key words: harmonious organization of the text, symmetry, asymmetry, expressiveness of the art text, information capacity. DOI 10.18522/1995-0640-2020-2-142-153